2020
DOI: 10.17159/sajs.2020/8531
|View full text |Cite
|
Sign up to set email alerts
|

‘Preventing the next pandemic’ – A 2020 UNEP Frontiers Series Report on zoonotic diseases with reflections for South Africa

Abstract: Zoonoses account for about 25% of the infectious disease burden in low-income countries. 1 Poverty might increase the risk for zoonotic disease where the active human-livestock and human-wildlife interfaces can increase the likelihood of disease transmission. 1 A combined disease burden exists for people in areas such as tropical and subtropical Africa, where there is likelihood of co-infection with zoonotic diseases and other pathogenic or infectious diseases, such as malaria, tuberculosis and HIV. 1 Many end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Alpha-coronaviruses cause respiratory diseases in humans and gastroenteritis in animals, while beta-coronaviruses are responsible for MERS’ emergence SARS, and COVID-19. γ-Coronavirus is a virus that causes avian infectious bronchitis disease in birds and chickens, and Δ-coronavirus is found in birds and mammals (Wernecke et al 2020 ). The novel coronavirus is a member of the genus β-coronavirus (Zhu et al 2020), with a high spreading velocity, identified as being transmitted via close contact.…”
Section: Coronavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-coronaviruses cause respiratory diseases in humans and gastroenteritis in animals, while beta-coronaviruses are responsible for MERS’ emergence SARS, and COVID-19. γ-Coronavirus is a virus that causes avian infectious bronchitis disease in birds and chickens, and Δ-coronavirus is found in birds and mammals (Wernecke et al 2020 ). The novel coronavirus is a member of the genus β-coronavirus (Zhu et al 2020), with a high spreading velocity, identified as being transmitted via close contact.…”
Section: Coronavirusesmentioning
confidence: 99%
“…To overcome further zoonotic and pandemic outbreaks, global cooperation toward legislative action to prevent the destruction of the natural habitats for unsustainable farming, mining, and building housing must move to sustainable pathways. Official and private sectors must cooperate toward working with the environment (Wernecke et al 2020 ; Sharun et al 2021 ). COVID-19 and public awareness should be part of the official and social media mainstream of conversations and delegations to be part of the soft power effect on policymakers and other governments and non-governmental organizations’ activities.…”
Section: Post-covid-19 Strategymentioning
confidence: 99%
“…Some of the changes in interaction patterns are caused by environmental changes due to global climate change which alters the environments in which human and other organism interact [ 1 , 2 , 3 , 4 ]. Other gradual or sudden changes in human social processes, such as changes in the meat industry or military conquests can also lead to zoonotic pandemics and novel human infectious diseases if they lead to novel encounters with non-human animals and other organisms [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Theoretic frameworks for the study of zoonotic infections that incorporate measures of human social processes can help us understand, predict and address zoonotic pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…As a considerable body of past research shows [ 10 , 13 , 50 ], there is every reason to predict that the combined and interacting impacts of economically-driven human incursions into, and the redevelopment of, forestlands, savannahs, and other areas where potential vectors and potential emerging pathogens exist; the ecological interface between industrialized animal husbandry and naturally occurring wildlife; the commodification and privatization of sources of water and of aquatic food chains and destruction of aquatic ecosystems; and global climate change will lead to major future zoonotic pandemics that may well be socially disruptive [ 51 , 52 , 53 ]. Further, as has occurred in the United States, France, and Brazil during the COVID-19 pandemic, pandemic related socioeconomic disruptions may interact with pre-existing social and political inequities and/or pre-existing political divisions to render public health policy and practice a contentious political issue.…”
Section: Introductionmentioning
confidence: 99%
“…PWUD are at an increased risk of COVID-19 transmission and infection and are more likely to be hospitalized for severe symptoms [5,6]. Given the severity of this ongoing public health crisis and the likelihood that further pandemics will take place in coming decades [7][8][9][10][11][12][13], it is imperative to understand how PWUO have dealt with the physical and psychological changes brought on by the COVID-19 pandemic, particularly in response to stay-at-home orders that limit in-person interactions.…”
Section: Introductionmentioning
confidence: 99%